EFFECT OF FMD VACCINATION ON SEMEN GHARACTERISTICS IN HOLSTEIN FRIESIAN BULLS - SAHA, SUJIT; MISHRA, G K; SINGH, R B; SHUKLA, M K; TIWARl, RITESH; SAXENA, S K (The Indian Journal of Animal Reproduction, 2011)
The present study was designed to investigate the effect of Foot and Mouth disease {FM □) vaccination onsemen production performance and quality parameters on the basis of semen collected from 25 Holstein Friesianbulls maintained at Animal Breeding Centre, Salon, Rae Bareli district of Uttar Pradesh during 2008 and 2009. Theresults indicated that ejaculate volume and initial motility differ significantly between pre and post vaccinationperiod, while no significant difference was evident with respect to concentration and total sperm output. But for allthe parameters maximum deterioration was noticed up to first 10 days post vaccination period. There was asignificant change (p
Keywords: Holstein Friesian; Semen production; Semen quality; FM □ vaccination